Managing innovation: a case study on the Nintendo Wii - Brignoli, Nicolo' (2008)
The goal of this exploratory case study (Yin 1994) is to understand how Nintendo manages innovation, and in particular how it managed the development of the Wii. Indeed, Nintendo has always been regarded as a creative and innovative firm. However, its internal practices and the innovative nature of its products have yet to be addressed from an academic viewpoint. This research does find that Nintendo managed the development of the Wii following the Blue Ocean Strategy approach (Kim & Mauborgne 2005). This substantiates in delivering value innovation and creating an uncontested market (the blue ocean) by the innovative firm. Moreover, the research provides useful insights on six topics coded from the interviews collected. Topics involve [1] the business strategy followed by the firm; [2] its business values; [3] the role of some key persons of the firm, namely its President Satoru Iwata and the Manager of the Entertainment Analysis Division, Shigeru Miyamoto; [4] an analysis of some organisational practices that enable innovation; [5] the role and support provided by top management; and finally the effectiveness of [6] Nintendo's tuning with the market.